Acute Kidney Injury, Mild Cognitive Impairment, and Dementia: A Cohort Study of Patients from SPRINT - Kristen L. Nowak; Anna Ostrow; Ester S. Oh; Zhiying You; Michel Chonchol (Kidney Medicine, 2025)
Rationale & Objective: It is well accepted that acute cognitive dysfunction and delirium can occur with severe acute kidney injury (AKI). Recent evidence has indicated AKI can contribute to incident dementia years later. However, these observations were limited by lack of adjudication in most of these studies and greater severity of AKI. Study Design: A retrospective cohort study. Setting & Participants: 8,148 older adults at high cardiovascular risk enrolled in the Systolic Blood Pressure Intervention Trial (SPRINT). Predictor: Adjudicated AKI as a time-varying predictor. Outcomes: Incident mild cognitive impairment (MCI), probable dementia, and their composite. Analytical Approach: Cox proportional hazard models. Results: Participants were 68 ± 9 years, 65% male, 28% with prevalent chronic kidney disease), with a median (interquartile range) follow-up time for the composite of 4.0 (2.1-5.4) and 4.6 (3.6-5.9) years in the AKI and non-AKI groups, respectively. The incidence rate of MCI, probable dementia, and their composite was higher in participants who experienced an AKI event (n = 270). In the fully adjusted model, AKI was positively associated with probable dementia (hazard ratio, 1.72; 95% CI, 1.07-2.75) and the composite outcome (1.43 [1.01-2.04]). Limitations: AKI before baseline was not captured; retrospective and associative. Conclusions: Adjudicated AKI, which was largely mild and reversible, was independently associated with increased risk of probable dementia and the composite of probable dementia and MCI in older adults at high cardiovascular risk. Plain Language Summary: It is well accepted that acute cognitive dysfunction and delirium can occur with severe acute kidney injury (AKI), and recent evidence has indicated that AKI can contribute to new onset of dementia years later. We examined whether having an AKI increased risk of adverse cognitive outcomes among 8,148 older adults at high cardiovascular risk enrolled who participated in the Systolic Blood Pressure Intervention Trial. AKI, although generally mild and reversible, independently associated with increased risk of probable dementia and a combined endpoint of probable dementia and mild cognitive impairment. These results suggest that cognitive function should be monitored following AKI in this patient population.